Solution:We can solve this equation by factorization as we did in a previous tutorial but it will take alot of time so I am going to solve this by using the Quadratic Formula:= = = = The solution of x is: ,

Solution:This type of equation can be factored easily, so there is no need to try completing-square or Quadratic formula.x^2 - 3x - 4 = 0(x+1) (x-4) = 0x + 1 = 0 or x - 4 = 0
x =...

Solution:This equation can be solved either by completing-square method or by using the Quadratic formula. The Quadratic formula ,in this case, is a better option as it leads to the answer more faster .The solution is

Solution:The solution to this problem is quite easy. As we can see the above statement has already been factorized for us. All we have to do here is solve the factors separately .(x+1) (x-3)=0x + 1=0 or x...

This equation is quite simple and we have two quick and easy ways to arrive at the desired solution.Solution:
Method 1:By taking square root on both sides we get:Method 2:By using formula in the above equation we get:
where...

Solution:The solution to this problem is quite simple.... Say r is a real root. Then we haveFor m = 2, there is a real root r = 2. But the sum of the roots is 3+i. From this, the second...

Solution:The solution to this problem is quite simple.....The two solutions are:

Solution:The solution to this problem is quite simple....